‘Warrior-women’ in Viking Age Scandinavia? A preliminary archaeological study - Gardeła, Leszek (Institute of Archaeology Rzeszów University, 2013)
This paper seeks to provide a new contribution to the debates on Viking Age women by focusing on a rather controversial notion of ‘female warriors’. The core of the article comprises a preliminary survey of archaeological evidence for female graves with weapons (axes, spears, swords and arrowheads) from Viking Age Scandinavia. Attention is focused not only on the types of weapons deposited with the deceased, but first and foremost on the meanings which similar practices may have had for the past societies. The author discusses why, where and how the weapons were placed in female graves and attempts to trace some patterns in this unusual funerary behaviour. In addition to exploring the funerary evidence, the iconographic representations of what could be regarded as ‘female warriors’ are also briefly considered. Lastly, a few remarks are also made on the notion of armed women in the textual sources.
Wojownicze kobiety w wikińskiej Skandynawii? Wstępne studium archeologiczne
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Viking Age; Scandinavia; women; weapons; funerary practices; atypical burials